The Influence Of Financial Knowledge, Financial Attitudes, And Personality On Financial Management Behavior (Student of the Faculty of Economics, Department of Management, Bachelorwiyata Tamansiswa University) - Ika Nurmala; Sri Hermuningsih; Gendro Wiyono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of Financial Knowledge, Financial Attitudes and Personality on Financial Management Behavior (Students of the Faculty of Economics, Management Department, Bachelorwiyata University of Tamansiswa Yogyakarta). This research is descriptive in nature with a quantitative method using the lemeshow formula with a sample size of 96 respondents. The research results prove that financial knowledge and personality influence financial management behavior, while financial attitudes do not influence financial management behavior.